Enzymatic Changes In Carrot Roots Induced By Erwinia Carotovora Var. Carotovora - V.K. PARTHIBAN; V.PRAKASAM; K. PRABAKAR (International Journal of Pharma and Bio Sciences, 2012)
Soft rot bacterium causes maceration of tissues due to the activity of various pectolytic enzymes and hence the activity of different pectic enzymes viz., poly galacturanase, pectin methyl esterase, pectin transeliminase and pectate lyase was studied. The activity of all the four enzymes increased from first day after inoculation and decreased on fifth day of inoculation in the carrot roots with all the three bacterial isolates. Among the three, the Coimbatore isolate was found to be more virulent in producing enzymes. The enzyme activity increased from first day after inoculation to fourth day and the activity decreased on the fifth day. Coimbatore isolate was found to produce more of the all pectolytic enzyme studied. When the virulence was compared with the capacity to produce pectolytic enzymes as a tool it could be concluded that the Coimbatore isolate was more virulent among the three isolates tested.